Peningkatan Motivasi Belajar Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Melalui Media Pembelajaran Power Point pada Peserta Didik Kelas V Sekolah Dasar - Basri Basri (Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to determine the increase in motivation to learn Islamic religious education and ethics subjects through PowerPoint learning media in class V students of SD IT Wihdatul Ummah, Takalar Regency. The type of research used in this study was Classroom Action Research. The research was located at SD IT Wihdatul Ummah, Takalar Regency, with ten students as the subjects in class V. The instruments used were in the form of learning motivation observation sheets and PowerPoint media observation sheets. Furthermore, the analytical technique used in this study was observational data analysis on learning motivation. The study concluded that media exposure significantly increased students' motivation to learn about Islamic religious education and ethics from cycle to cycle. The PowerPoint media can improve student learning motivation in grade V students of SD IT Wihdatul Ummah, Takalar Regency.